1992
DOI: 10.3147/jsfp.27.131
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Quinolone antibacterials against Selected Fish Pathogens.

Abstract: A comparison was made of the in vitro activities of five quinolone antibacterials (nalidixic acid, piromidic acid, oxolinic acid, flumiquine and miloxacin) currently used in aquaculture in Japan and five newer quinolones (ofloxacin, norfloxacin, enoxacin, ciprofloxacin and tosufloxacin), against selected fish bacterial pathogens.Of the earlier quinolones, flumiquine and oxolinic acid showed the highest bacteriostatic and bactericidal activities against Gram-negatives.The newer quinolones, however, showed consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Recent publications seem to indicate that the antibacterial properties of several quinolones are greatly influenced by the presence of cations in concentrations equal to those in seawater. Palmer et al (1992) demonstrated a significant influence of magnesium ions on the in vitro effect of`older' quinolones, but found a less pronounced effect on the newer fluoroquinolones. Pursell et al (1995) found in a 72 h assay an 8-fold increase in MBC (minimum bactericidal concentration) against A. salmonicida for flumequine when divalent cations were present in the medium compared to the same assay without these cations.…”
Section: Quinolonesmentioning
confidence: 95%
“…Recent publications seem to indicate that the antibacterial properties of several quinolones are greatly influenced by the presence of cations in concentrations equal to those in seawater. Palmer et al (1992) demonstrated a significant influence of magnesium ions on the in vitro effect of`older' quinolones, but found a less pronounced effect on the newer fluoroquinolones. Pursell et al (1995) found in a 72 h assay an 8-fold increase in MBC (minimum bactericidal concentration) against A. salmonicida for flumequine when divalent cations were present in the medium compared to the same assay without these cations.…”
Section: Quinolonesmentioning
confidence: 95%